Oribatid mites (Acari, Oribatida) of plain area of the Southern European Russia - Lebedeva, Natalia V.; Poltavskaya, Marina P. (Zootaxa, 2013)
The paper is devoted to the fauna of oribatid mites (Acari: Oribatida) mostly of a plain area of the Southern European Russia. The most updated taxonomic list of oribatid mite taxa compiled from the original authors' data collected after sampling soil, nests and plumage of birds, as well as published sources is presented. It includes 256 species of oribatid mites belonging to 72 families. Twenty species and one family of oribatid mites are recorded for the first time at the research territory. The abundance of mites in the soil is also provided for selected species.